(untitled) (Indian Journal of Case Reports, 2024)
Anesthetic management of cardiac disorders in pregnancy has always been complicated and challenging. Peripartum cardiomyopathy (PPCM) is a rare but extremely fatal, life-threatening disease affecting the parturient with mortality rates as high as 35–50%. Developing in late pregnancy or immediately after delivery endangers not only the mother but also the baby. We report here a case of a 27-year-old female parturient presenting at 38 weeks of gestation for cesarean delivery with labor pain with recently diagnosed PPCM (moderate mitral regurgitation, mild tricuspid regurgitation, and 2D ejection fraction of 55–60%) complicated by severe pre-eclampsia with previous lower segment cesarean section. She developed cardiac failure just before the induction of anesthesia. She was successfully resuscitated, operated under general anesthesia, and shifted to the critical care unit for further management.